Exploring Religious Scholars Perspectives on Child Physical Abuse: A Case Study of District Malakand - Ullah, Irfan; Sher Shah; Hamid Alam; Sibgaht Ullah, (Pakistan Review of Social Sciences (PRSS), 2023)
Abstract Child physical abuse is a significant global concern, and its prevalence varies across cultures and societies. This case study focuses on District Malakand, exploring the perspectives of religious scholars on child physical abuse. The study is qualitative in nature, utilizing purposive sampling to select 10 religious scholars as respondents. Islamic teachings emphasize the protection and welfare of children, promoting kindness and mercy. While Islam does not support physical punishment, some mild forms of discipline are allowed under specific circumstances. The findings reveal that religious scholars and teachers are not in favor of physical abuse due to its negative psychosocial impacts on the child's development. The study sheds light on the need to eradicate physical abuse from educational institutions and homes to create a nurturing environment for children in accordance with Islamic teachings. Keywords: Physical Abuse, Child, Islamic, Malakand, Punishment